Corrigendum - Cai, Yida (Finnish Journal of Linguistics, 2024)
The author information in the book review “Dalrymple, Mary & Lowe, John J. & Mycock, Louise (eds.). 2019. The Oxford Reference Guide to Lexical Functional Grammar. Oxford: Oxford University Press. Pp. 835” published in the issue Vol. 35 (2022) of the Finnish Journal of Linguistics was incorrect, the correct information is “Dalrymple, Mary & Lowe, John J. & Mycock, Louise. 2019. The Oxford Reference Guide to Lexical Functional Grammar. Oxford: Oxford University Press. Pp. 835”. Consequently, the first sentence of the book review is “The Oxford reference guide to Lexical Functional Grammar is a volume offering wide-ranging and detailed information about Lexical Functional Grammar (LFG).”